MODEL ANALYSIS OF INTENTION TO USE E-COMMERCE GOJEK - Muhammad Mahdi, Arif Imam Suroso & Jokoratono (International Journal of Research Science and Management, 2018)
Go-jek application is a form of innovation in terms of public transportation services .The presence of this system has been interesting for the public, not only attract consumers to try service facilities, but also attract attention of ojek drivers conventional as evidenced by many ojek drivers move to join and use the the application. Inefficiency of ojek drivers conventional has become an opportunity for go-jek to innovate and create a system based on application that aimed at increasing value from ojek service. Although the presence of the internet benefits useful for users and company, but behavioral intention to use e-commerce does not appear automatically in users to use the technology directly, proven by many e-commerce application who was not welcomed by consumers to shove their intention to use his services. So what was the causes of someone intention to appear and use go-jek and be able to received by the consumers?.Hence intention behavior to use ecommerce drift researchers to run a research against someone intention at using the technology. If the factors that could encourage the intention of an individual to use a e-commerce was known, the company will capable of created a e-commerce technology platform that could encourage intention of the e-commerce consumers in indonesia to use it , which consisted of more than 100 million people and ready to transact with the 5 billion usd, so the company will have a opportunities and the potential to be successful.